Study on Morphometric Assessment of Adult Human Lumbar Vertebrae - Balu Gangaram Londhe; Rajendra Somnath Garud (Recent Developments in Medicine and Medical Research Vol. 3, 2021)
Low backache is most commonly experienced in the lumbar region of the human spine. Lumbar morphometry is important not only for understanding the biomechanics of the lumbar spine, but also for a variety of therapies aimed at stabilizing and correcting abnormalities. Aims and Objective: To access anatomical dimensions of lumbar vertebral body for preparation of spinal fixation devices. The study was carried out to prepare morphometric data on dimensions of lumbar vertebral body which can be used in clinical practice. An observational study was carried out in which 47 dry macerated adult human lumbar vertebral sets were directly examined and morphometric analysis was performed in preference to vertebral body. SPSS Ver.20 was used to process and analyse the data.To assess statistical differences, the ‘ANOVA’ and ‘Z test’ were used. Results: The superior surface’s antero-posterior (AP) diameter increased gradually from L1 to L5. However, the AP diameter of the inferior surface increased up to L4, but then decreased. Transverse measurements show a gradual upward increase from L1 to L5. The heights of the vertebral bodies fluctuated. Superior surface area (SA) gradually increases from L1 to L5.However, inferior surface area (IA) increases up to L4 and decreases at L5. Discussion and Conclusion: Except for the ‘posterior height’ of lumbar vertebral bodies, the study found highly significant differences in all vertebral dimensions. The generated results should be expanded to include a larger sample size as well as known sets of male and female lumbar vertebrae in a diverse population.